Advances in Radiation Protection in Oral and Dental Radiology: Pragmatic Approaches and Recent Innovations - Saiedeh Sadeghi; Nastaran Saeidi; Ali Salehi; Kamal Attari; Mohammad Ali Irani; Seyed Sasan Aryanezhad; Reza Malekzadeh; Reza Mahmoudi Anzabi (Frontiers in Biomedical Technologies)
Purpose: The utilization of Ionizing Radiation (IR) in diagnostic dental techniques poses inherent risks, especially when patients are exposed to it repeatedly. Therefore, it is crucial to continuously evaluate and improve the measures taken to protect individuals from the potentially harmful effects of ionizing radiation in dental radiology. This study desires to assess the advancements made in recent years regarding ionizing radiation protection measures in the field of dental radiology.